2010
DOI: 10.1088/0951-7715/23/4/r01
|View full text |Cite
|
Sign up to set email alerts
|

Dimension of non-conformal repellers: a survey

Abstract: This article is a survey of recent results on dimension of repellers for expanding maps and limit sets for iterated function systems. While the case of conformal repellers is well understood the study of nonconformal repellers is in its early stages though a number of interesting phenomena have been discovered, some remarkable results obtained and several interesting examples constructed. We will describe contemporary state of the art in the area with emphasis on some new emerging ideas and open problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 37 publications
1
32
0
1
Order By: Relevance
“…In fact, there are many settings in which s(Λ) is equal to the Hausdorff dimension. See Section 5 and a survey [CP10] for more details on the number s(Λ). From its definition, it follows that s(Λ) varies upper semi-continuously under small perturbations of the repeller Λ.…”
mentioning
confidence: 99%
“…In fact, there are many settings in which s(Λ) is equal to the Hausdorff dimension. See Section 5 and a survey [CP10] for more details on the number s(Λ). From its definition, it follows that s(Λ) varies upper semi-continuously under small perturbations of the repeller Λ.…”
mentioning
confidence: 99%
“…Recently, in [9] the authors introduced the super-additive topological pressure, and showed that the zero of super-additive topological pressure gives a lower bound of the Hausdorff dimension of repellers. We refer the reader to [10] and [5] for a detailed description of the recent progress in dimension theory of dynamical systems.…”
Section: Introductionmentioning
confidence: 99%
“…The question of which dynamical systems have ergodic invariant measures of full Hausdorff dimension has generated substantial interest over the past few decades, see e.g. [4,9,17,18,21,24,25,27,30,31,32,33,42,45,52,55], as well as the survey articles [7,13,22,51] and the books [5,6]. Most of the results are positive, proving the existence and uniqueness of a measure of full dimension under appropriate hypotheses on the dynamical system.…”
Section: Introductionmentioning
confidence: 99%
“…Progress beyond these cases, and in particular in the case where the system is expanding but may have different rates of expansion in different directions, has been much slower and of more limited scope, see e.g. [7,13,22,51]. Such systems, called "expanding repellers", form another large and much-studied class of examples.…”
Section: Introductionmentioning
confidence: 99%